Women's Periodicals and Print Culture in Britain, 1940s-2000s : The Postwar and Contemporary Period. - Forster, Laurel; Hollows, Joanne (Edinburgh history of women's periodical culture in Britain., 2020)
Women's Periodicals and Print Culture in Britain, 1940s-2000s draws attention to the wide range of postwar print cultures for women. The collection spans domestic, cultural and feminist magazines and extends to ephemera, novels and other printed matter as well as digital magazine formats.